SUPPORTING STUDENT’S SPEAKING SKILL DURING PANDEMIC - Arjulayana; Zainal Rafli; Ratna Dewanti (UICELL, 2021)
Since late 2019 the world is transmitted of corona virus diseases- 19. During this pandemic many sectors in the world are changing. Teaching and learning model also changed, almost 4 semesters university may not implement face to face/ direct teaching and learning process, but it should be applied online. Speaking is one of the most fundamental language skills which also used to apply in online, and during this remote learning speaking practice is quite tricky, because it’s need to be responded directly and showing speaker’s gesture and eye contact. Synchronous and asynchronous speech online is needed to overcome that situation. In synchronous students and lecturer are doing virtual discuss and speaking practice through Google meet, and the asynchronous process is done by recorded video or voice then students need to submit through Google classroom or Microsoft Team, while in synchronous model students and lecturer are doing virtual meeting and interact directly. The method of this research is qualitative descriptive method to explain how speaking online is implemented in process of teaching and learning during this pandemic. There were 115 students as a sample, and the data collection is taking through survey, interview and test. based on the result, it shows that online teaching and learning speaking through synchronous model is the most effective, because in this model lecturer can give feedback automatically while doing virtual learning, and students also are able to communicate directly and practice in the spot time with doing self-repair. Beside of that, teaching speaking also can be implemented through video record with simulate the picture while speaking, that model is quite effective to treat student’s speaking skill and they are able to speak and avoid their anxiety. Keywords: Speaking Skill, Pandemic, Synchronous, Asynchronous, Speaking Practice